Risk factors associated with the progression and metastases of hindgut neuroendocrine tumors: a retrospective study - Yoichiro Okubo; Rika Kasajima; Masaki Suzuki; Yohei Miyagi; Osamu Motohashi; Manabu Shiozawa; Emi Yoshioka; Kota Washimi; Kae Kawachi; Yoichi Kameda; Tomoyuki Yokose (BMC Cancer, 2017)
Abstract Background The worldwide incidence of neuroendocrine tumors (NETs) has increased remarkably, with the hindgut being the second most common site for such tumors. However, the mechanisms underlying progression and metastasis of hindgut NETs are unclear. A retrospective study was conducted to elucidate these mechanisms. Methods Clinicopathological data of cases of hindgut NET between April 1996 and September 2015 were analyzed, retrospectively. Patients with neuroendocrine carcinoma were excluded. Formalin-fixed paraffin-embedded tissues of hindgut NET cases were subjected to detailed morphometric and immunohistochemical analyses. Statistical analyses were performed using the non-parametric Mann-Whitney U test, Spearman’s correlation coefficient, and chi-squared test. Multivariate logistic regression analysis was conducted as appropriate for the data set. Results Fifty-six hindgut NET cases were considered. Microvessel density and lymphatic microvessel density were identified as significant risk factors for venous and lymphatic invasion. There was a positive correlation between microvessel density and the maximum tumor diameter. Multivariate logistic regression analysis revealed that the maximum tumor diameter alone was an independent predictor of lymph node metastasis, whereas lymphovascular invasion and MVD was not the predictor of lymph node metastasis. There were no significant correlations between the Ki-67 labeling index and any of the parameters evaluated including age, sex, the maximum tumor diameter, venous invasion, lymphatic invasion, microvessel density, lymphatic microvessel density, and lymph node metastasis. Conclusions Angiogenic mechanisms may play important roles in the progression of hindgut NET. Otherwise, the maximum tumor diameter alone was an independent predictor of lymph node metastasis in hindgut NETs. Moreover, our study raises the question of whether the presence of lymphovascular invasion, in endoscopically obtained hindgut NET tissues, is an absolute indication for additional surgery or not.